The effects of the ambient liquid medium on the ablation efficiency, size and stability of silver nanoparticles prepared by pulse laser ablation in liquid technique - Al Azawi, M. A. (Penerbit UTM Press, 2016)
Silver (Ag) nanoparticles (NPs) were synthesized by pulsed laser (Nd:YAG, 1064 nm) ablation of individual target in various solutions. The influence of deionized water (DIW), ethanol and Polyvinylpyrrolidone (PVP) as ambient medium on the fundamental aspects such as ablation efficiency, particle size and stability of Ag NPs was studied. UV-vis spectrophotometer and transmission electron microscopy (TEM) were used to study the optical characterization and morphological analysis of all the synthesized samples, respectively. Preparation in DIW was carried out as a reference sample. The experiments demonstrated that ablation efficiency and stability of NPs in ethanol medium are lowest than those prepared in PVP medium and the reference sample. PVP medium led to higher stability, lower ablation efficiency and finer average particle size compared to reference sample.